Temperature‐Related Effects on Disease Susceptibility and Immune Response in Redband Trout ( Oncorhynchus mykiss gairdneri ) Following Challenge With Flavobacterium columnare - Joshua P. Egan; Jie Ma; Veronica L. Myrsell; Zhongqi Chen; Jonathan Masingale; Christopher C. Caudill; Timothy Boyle; Julianna Browning; Shawn R. Narum; Kenneth D. Cain; Paul A. Hohenlohe (Journal of Fish Diseases, 2025)
Heat stress can increase disease risk in fishes by reducing immune function. Interactions between redband trout ( Oncorhynchus mykiss gairdneri ) and Flavobacterium columnare , a causative agent of columnaris disease, provide an opportunity to investigate the effects of temperature on immune function and disease resistance during periods of thermal stress. We conducted three trials to characterise differences in immune function and mortality between redband trout held at 18°C and 21°C following challenge with F . columnare . In trial 1, cumulative per cent mortality (CPM) was low and not statistically different between 18°C and 21°C. In trials 2 and 2, we administered higher challenge doses and observed increased CPM overall and significantly greater CPM at 21°C than 18°C. Redband trout upregulated il‐8 , tnf‐α , igm and igt following infection by F . columnare , suggesting that all of these genes may be involved in immune responses to F . columnare infection. We found no differences in the strength of the immune responses between fish held at 21°C versus 18°C. This indicated that 21°C did not elicit sufficient thermal stress to impair immune function and that increased CPM at 21°C versus 18°C was due to enhanced F . columnare virulence.